Implementasi Algoritma K-Means Dalam Clustering Rejection Patung Tangan Keramik (Studi Kasus : PT.Mark Dynamics Indonesia,Tbk) - Andreas Gerhard Simorangkir; Erlinda Simamora; Siska Kristiana Simanullang; Desi Simanjuntak; Vini Kristin Septiani Situmorang; Efori Bu’ulolo (Journal of Information System Research (JOSH), 2022)
PT. Mark, Dynamics Indonesia Tbk is one of the companies engaged in the printing of Ceramic Hand Sculptures. This Ceramic Hand Sculpture already exists in several cities outside the city even outside the company PT Mark Damica Indonesia. request orders and various customers who are in cities outside the city and even abroad. In the process of making Eating Hand Ceramics, this company has a problem, namely the Rejection of the Ceramic Hand Sculpture that is produced. Thick Bergolan and Sompel This research was conducted for the Clustering Rejection of the Ceramic Hand Sculpture based on the items that have been determined by Eemal/Company Leader of PT Mark Dynamics Indonezia Tbk. Clustering Rejection of Ceramic Hand Sculpture ETMark Dynamics Indonesia Tbk still takes a long time To assist the company ETMark Dynamics Indonesia Thk in the process of Clustering Rejection of Ceramic Hand Sculpture, combined with an implementation based on the tem-sem that has been determined using the K-Means Algorithm.